Repeatability of measurements of removal of mite-infested brood to assess Varroa Sensitive Hygiene. Issue 5 (20th October 2017) - Villa, Jose D; Danka, Robert G; Harris, Jeffrey W
Abstract : Varroa Sensitive Hygiene (VSH) is a useful resistance trait that honey bee ( Apis mellifera ) breeders could increase in different populations with cost-effective and reliable tests. We investigated the reliability of a one-week test estimating the changes in infestation of brood introduced into colonies highly selected for VSH and into unselected colonies. We repeated tests on the same 32 colonies up to five times and compared variation within colonies and between colonies of the two types. As expected, selected VSH colonies decreased infestation much more than unselected colonies (−77 vs. −5%, p  < 0.0001) and also produced final mite populations in the introduced comb with higher infertility (41 vs. 16%, p  = 0.002). The variance in percentage decrease in infestation of introduced brood within colonies was higher in the unselected group. These variances can be used to estimate the number of repeated tests required to detect true differences between colonies. In an already selected VSH population, potentially useful differences between colonies ( ca. 45%) can be detected with only one measurement per colony. Multiple measurements of colonies (up to 5 replications) are required to detect similar differences between colonies in less selected and more variable populations.